Introducing the Lantang Lantang Pangang performance: one of the oldest puppet performance rituals in Indonesia - Andi Baetal Mukadas; Faizal Erlangga Makawi; Hasbi Hasbi (Pascasarjana Institut Seni Indonesia Surakarta, 2024)
The Lantang lantang pangang is an integral part of the Toraja funeral ceremony, however, in recent times the knowledge of this puppet performance has changed significantly. This study aims to introduce and preserve the significance of lantang lantang pangang in puppet performances for the Toraja people. The method used is a qualitative study using a cultural anthropology that emphasizes social values and symbolism. The findings show that; (1) Lantang lantang pangang has a deep-rooted history dating back to the 9th century; (2) its dual role in funerals and as Toraja-style souvenirs; (3) its unique puppet characteristics; (4) the traditional puppet performance was carried by the high social status of Toraja people;(5) the performance reflects on the profile of the deceased and for entertainment purpose for grieving families; (6) Integrating it into school education is vital to preserving this culture. This study will have a historical significance that emphasizes the social context of funeral ceremonies and puppet performances to preserve cultural heritage.